Court-ordered forensic psychiatry treatment in prison: determinants of outcome and risk mitigation - Weber, Kerstin; Morier, Sandrine; Menu, Christophe; Bertschy, Philippe; Herrmann, François R.; Giannakopoulos, Panteleimon (Frontiers in Psychiatry, 2024)
Background: Court-ordered forensic psychiatry treatments (COT) are specifically designed to reduce the risk of violence in mentally disordered offenders. Given their high costs and ethical issues, mental health professionals need admission criteria to be able to select those candidates with optimal benefit. This study analyses offender-related and treatment-related determinants of COT outcome and risk mitigation. Methods: This two-year longitudinal study assessed the evolution of 117 adult offenders admitted to a specialized medium-security forensic psychiatry clinic. Treatment outcome included court-ordered discharge locations and the Historical Clinical Risk Management (HCR) score evolution. Treatment progress was assessed every six months across five time-points including measures of protective factors, work rehabilitation and security. Outcome determinants included psychiatric diagnosis and type of offence. Results: Discharge locations are predicted by pre-treatment risk level. Lower HCR scores are associated with discharge into low-security psychiatry wards independently of the psychiatric diagnosis. Risk reduction follows diagnosis-specific and offense-related patterns and reveals that mentally disordered offenders with Cluster B personality disorders or those sentenced for drug crimes are significantly less prone to benefit from COT. Conclusions: Our findings indicate that criminological characteristics at baseline as well as diagnosis of personality disorders are the main determinants of treatment outcome in our care setting. Inmates with concomitant higher violence risk at baseline and presence of Cluster B personality disorders might benefit the least from court-ordered forensic inpatient psychiatric care in prison.